Taming hyperactive hDNase I: Stable inducible expression of a hyperactive salt‐ and actin‐resistant variant of human deoxyribonuclease I in CHO cells. (6th February 2017) - Lam, Cynthia; Santell, Lydia; Wilson, Blair; Yim, Mandy; Louie, Salina; Tang, Danming; Shaw, David; Chan, Pamela; Lazarus, Robert A.; Snedecor, Brad; Misaghi, Shahram
Abstract : While the most common causes of clonal instability are DNA copy number loss and silencing, toxicity of the expressed protein(s) may also induce clonal instability. Human DNase I (hDNase I) is used therapeutically for the treatment of cystic fibrosis (CF) and may have potential benefit for use in systemic lupus erythematosus (SLE). hDNase I is an endonuclease that catalyzes degradation of extracellular DNA and is inhibited by both salt and G‐actin. Engineered versions of hDNase I, bearing multiple point mutations, which renders them Hyperactive, Salt‐ and Actin‐Resistant (HSAR‐hDNase I) have been developed previously. However, constitutive expression of HSAR‐hDNase I enzymes has been very challenging and, despite considerable efforts and screening thousands of clones, no stable clone capable of constitutive expression had been obtained. Here, we developed a regulated expression system for stable expression of an HSAR‐hDNase I in Chinese Hamster Ovary (CHO) cells. The HSAR‐hDNase I clones were stable and, upon induction, expressed enzymatically functional protein. Our findings suggest that degradation of host's DNA mediated by HSAR‐hDNase I during cell division is the likely cause of clonal instability observed in cells constitutively expressing this protein. Purified HSAR‐hDNase I was both hyperactive and resistant to inhibition by salt and G‐actin, resulting in an enzyme having ca. 10‐fold greater specific activity and the potential to be a superior therapeutic agent to wild type (WT) hDNase I. Furthermore, the ability to regulate hDNase I expression has enabled process development improvements that achieve higher cell growth and product titers while maintaining product quality. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 32:523–533, 2017